2011
DOI: 10.1002/jbm.a.33250
|View full text |Cite
|
Sign up to set email alerts
|

Starburst low‐molecular weight polyethylenimine for efficient gene delivery

Abstract: Low-molecular weight polyethylenimine (LMW PEI) shows the advantage of low-cytotoxicity, but has been inefficient in gene delivery as a consequence of the low-charge density. A number of previous studies employed the approach of crosslinking to solve this problem. In this study, a starburst LMW PEI gene vector has been developed. It has a polyamidoamine (PAMAM) core conjugated with a shell composed of LWM PEI and polyethylene glycol (PEG), that is PAMAM-PEI-PEG. Plasmid DNA (pEGFP-N1) and human cervix epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The non-observed toxicity of star-shaped FA-CD-PLLD could be attributed to its lower molecular weight (less than 5 KDa) and the characteristic of molecular structure, such as the biodegradability and carrying a positive charge only on the surface. The biodegradability of FA-CD-PLLD can also promote its elimination from organism and thereby enhance the in vivo biocompatibility [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The non-observed toxicity of star-shaped FA-CD-PLLD could be attributed to its lower molecular weight (less than 5 KDa) and the characteristic of molecular structure, such as the biodegradability and carrying a positive charge only on the surface. The biodegradability of FA-CD-PLLD can also promote its elimination from organism and thereby enhance the in vivo biocompatibility [35]. …”
Section: Discussionmentioning
confidence: 99%
“…After grafted with PEI 1800 arms, the star‐shaped SCP‐based polyplexes had two orders of magnitude higher than DNA/PEI 1800 polyplexes, which was ascribed to the higher molecular weight by the grafting arms. Interestingly, PEGylation via host–guest interactions did not decrease the transfection efficiency, which was related to the star‐shaped architecture of polycations . It was also reported that PEGylation based PAMAM dendrimers could increase the transfection efficiency dendrimers .…”
Section: Resultsmentioning
confidence: 84%
“…Pluronic P123 with formula EO 20 -PO 70 -EO 20 , which has a proper hydrophile lipophilic balance (HLB) value, can be degraded to decrease cytotoxicity after cell uptake. Studies [10] showed that although the PEI derivate P123-PEI synthesized by cross-linking LMW-PEI with P123 had good degradability and low cytotoxicity, the transfection efficiency of the polymeric gene vector is not high enough.…”
Section: Introductionmentioning
confidence: 99%